Evidence of double layer/capacitive charging in carbon nanomaterial-based solid contact polymeric ion-selective electrodes. Issue 62 (13th July 2016) - Cuartero, Maria; Bishop, Josiah; Walker, Raymart; Acres, Robert G.; Bakker, Eric; De Marco, Roland; Crespo, Gaston A.
Abstract : We report on the first direct spectroscopic evidence of the capacitive ion-to-electron transducing mechanism of carbon nanomaterials in solid contact polymeric ion-selective electrodes (SC-ISEs). Abstract : This paper presents the first direct spectroscopic evidence for double layer or capacitive charging of carbon nanomaterial-based solid contacts in all-solid-state polymeric ion-selective electrodes (ISEs). Here, we used synchrotron radiation-X-ray photoelectron spectroscopy (SR-XPS) and SR valence band (VB) spectroscopy in the elucidation of the charging mechanism of the SCs.